Penggunaan Metode Trash trap dalam Kegiatan Clean Up di Daerah Sungai Paoq Pampang Desa Labuhan Haji, Kabupaten Lombok Timur - Muhammad Iman Darmawan; Shofwatunnida’; Putra, Agus Muliadi; Baiq; Husnayati; Dwi; Haerudin (Universitas Hamzanwadi, 2024)
Maintaining good hygiene is crucial for both the environment and daily life. One of the neighborhoods with a sizable amount of trash these days is the river. It is an expression of the actions of those who purposefully throw trash into the river. Seventy percent of the entire rubbish is caught by the trash trap, as can be observed by the garbage composition in the river, which is primarily plastic. One of the beneficial initiatives that benefits the community and the ecology around the river is the river clean-up campaign. The trash trap method—a waste collection technique that uses a sewer to keep waste from leaking into the sea—is used to clean up the Paoq Pampang River. Keyword: Garbage, river, trash trap